Sensorimotor Coding of Vermal Granule Neurons in the Developing Mammalian Cerebellum - Markwalter, Kelly H. (J Neurosci, 2019)
The vermal cerebellum is a hub of sensorimotor integration critical for postural control and locomotion, but the nature and developmental organization of afferent information to this region have remained poorly understood in vivo. Here, we use in vivo two-photon calcium imaging of the vermal cerebellum in awake behaving male and female mice to record granule neuron responses to diverse sensorimotor cues targeting visual, auditory, somatosensory, and motor domains. Use of an activity-independent marker revealed that approximately half (54%) of vermal granule neurons were activated during these recordings. A multikernel linear model distinguished the relative influences of external stimuli and co-occurring movements on neural responses, indicating that, among the subset of activated granule neurons, locomotion (44%–56%) and facial air puffs (50%) were more commonly and reliably encoded than visual (31%–32%) and auditory (19%–28%) stimuli. Strikingly, we also uncover populations of granule neurons that respond differentially to voluntary and forced locomotion, whereas other granule neurons in the same region respond similarly to locomotion in both conditions. Finally, by combining two-photon calcium imaging with birth date labeling of granule neurons via in vivo electroporation, we find that early- and late-born granule neurons convey similarly diverse sensorimotor information to spatially distinct regions of the molecular layer. Collectively, our findings elucidate the nature and developmental organization of sensorimotor information in vermal granule neurons of the developing mammalian brain. SIGNIFICANCE STATEMENT Cerebellar granule neurons comprise over half the neurons in the brain, and their coding properties have been the subject of theoretical and experimental interest for over a half-century. In this study, we directly test long-held theories about encoding of sensorimotor stimuli in the cerebellum and compare the in vivo coding properties of early- and late-born granule neurons. Strikingly, we identify populations of granule neurons that differentially encode voluntary and forced locomotion and find that, although the birth order of granule neurons specifies the positioning of their parallel fiber axons, both early- and late-born granule neurons convey a functionally diverse sensorimotor code. These findings constitute important conceptual advances in understanding the principles underlying cerebellar circuit development and function.